If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3(5 + -3x) = 5 7x + (5 * 3 + -3x * 3) = 5 7x + (15 + -9x) = 5 Reorder the terms: 15 + 7x + -9x = 5 Combine like terms: 7x + -9x = -2x 15 + -2x = 5 Solving 15 + -2x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2x = 5 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 5 + -15 -2x = 5 + -15 Combine like terms: 5 + -15 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 | | 7(1-5r)+6r=94 | | 6(9x+2)=54x-7 | | X/9=7/5 | | -(x-8)+4=2(-5.7)+x | | a(ax-a)+6(x+6)=0 | | x^2-5y^2-4x+4y-6=-6y^2-6y+10x-64 |